2007
DOI: 10.1002/adma.200701982
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Performance of Protein‐Resisting Surfaces at Ultra‐Low Protein Coverages using Kinesin Motor Proteins as Probes

Abstract: Surfaces resistant to protein adsorption are very desirable for a variety of applications in biomedical engineering and bionanotechnology, since protein adsorption is often the first step in a cascade of events leading to systems failure. Initial efforts to create adsorption-resistant surfaces succeeded in reducing the adsorption by 80% compared to untreated surfaces to 100 ng cm -2 by employing poly(ethylene glycol) coatings.[1]Recently, optimization of brush density and morphology has reduced adsorption to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
41
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 46 publications
4
41
0
Order By: Relevance
“…Based on landing rate measurements, 24 the concentration of this kinesin solution is 730±180nM in this stock solution.…”
Section: Methodsmentioning
confidence: 99%
“…Based on landing rate measurements, 24 the concentration of this kinesin solution is 730±180nM in this stock solution.…”
Section: Methodsmentioning
confidence: 99%
“…The protein resistance of POEGMA brushes has been confirmed by a number of groups, including Katira et al, who found that adsorption of kinesin was 20-fold lower on POEGMA surfaces compared to OEG-SH SAMs on gold. [55] SI-ATRP of OEGMA (and other monomers) is also compatible with soft-lithography; an ATRP initiator with a terminal thiol group was patterned on gold by microcontact printing (mCP), followed by SI-ATRP to yield micropatterns of POEGMA (Fig. 3A).…”
Section: Growth Of Poegma-functionalized Polymer Brushes On Surfacesmentioning
confidence: 99%
“…This polymer provides initiator groups for subsequent atom transfer radical polymerization 28 (ATRP). By ATRP, a ~200-nm-thick poly(ethylene glycol) methacrylate (PEGMA) top layer was deposited, which rendered the neuronal probe devices protein-resistant 28,29 (Fig. 1c).…”
mentioning
confidence: 99%